An Information System Model for Educational Management in Supply Chain According to Career standards on Thailand Qualifications Framework for Vocational Education - Artaphon Chansamut (International Journal of Supply Chain Management, 2021)
This research aims to 1) design and evaluate Information system model for educational Management in Supply Chain according to career standards on thailand qualifications Framework for vocational education. The sample groups were 5 experts in supply chain management, 5 experts in Information and technology and 5 experts on curriculum. The research sample totaling 15 experts. The research tool was questionnaire to system Model for educational Management in Supply Chain according to Career standards on thailand qualifications framework for vocational Education comprises six main components, namely Sub-components, Suppliers, Service provider ,Manufacturer, Finished product and customers .The data analyzed by using arithmetic mean and standard deviation. A Model of assessment system using Back-Box technique.The overall evaluation result Information system Model for educational Management in Supply Chain according to Career standards on Thailand Qualifications framework for vocational education, shows the overall rating mean of 3.78 suggesting that The framework aims to support sustainable information system development.